Pericardial Window Formation Complicated by Intrapericardial Diaphragmatic Hernia - Jeremy Docekal; Thomas Fabian (Case Reports in Surgery)
In rare circumstances, a diaphragmatic defect may allow for herniation of intra-abdominal contents into the pericardial space. These occurrences are exceedingly rare and may be due to trauma or congenital defects of the septum transversum or as the result of surgical procedures. We describe a 73-year-old female who presented with cardiac and abdominal symptoms one month after undergoing a subxiphoid pericardioperitoneal window for treatment and evaluation of a symptomatic pericardial effusion.